Exploring Synergies: The Benefits of Maize - Legume Intercropping Systems in Eastern Uganda - Godfrey, Kaiira Moses; Gilbert, Omiat Emmanuel; Nasser, Kasozi; Frank, Kagoda; Robert, Gidoi; Moses, Elesu (European Journal of Applied Sciences, 2025)
The study was carried out to investigate the agronomic and economic benefits of intercropping maize (Mz) with legumes. The experiment was arranged in RCBD with three replications during 2023 and 2024. The 8 treatments were conventional Mz (75 x 30cm), paired row (PR) Mz (100/50 x 30cm), 3 PR maize + 2 rows of each of groundnuts (Gn), soybeans (Sb) and beans (Bn) plus 3 pure legumes at 40x 10 cm. Results in 2023 and 2024 showed that PR maize + legumes significantly (P>0.05) increased maize plant height in both seasons, but the cobs per plant, 1000 seed weight and maize grain yield were not significant. During 2023, significant reductions were recorded in pods per plant (PP) and filled pods per plant (FPP). Percent filled pods (PFP) increased under Sb and reduced for Bn but was not significant for Gn. In 2024 the PP and FPP reduced for the intercrops while PFP were not significant. Height for the intercrops increased during 2023 and it raised only for Gn and soybeans in 2024. Legume intercrops yields declined during 2023 and 2024. The Partial land equivalent ratio (pLER) of Mz were less than unity during both seasons and Sb similarly recorded a low pLER during 2023 but a high pLER was recorded in 2024. Combined LER (cLER) for Mz and intercrops were significant (P>0.001) for groundnuts during both seasons. Mz/Gn recorded higher MAI & MEY during 2023 while Mz + Bn and Mz + Sb had low values. Mz/Gn produced high TMGYE during 2023 and the other treatments were low. Higher Aggresivity (A) was recorded under Mz/Gn during 2023 and 2024 with low A under Mz/Sb and Mz/Bn in 2024. The results indicate that Mz + Gn had higher synergies amongst the cropping combinations and recommended.